Exploring the self-efficacy beliefs of Vietnamese pre-service teachers of English as a foreign language. (February 2021) - Hoang, Thinh; Wyatt, Mark
Abstract: There is growing evidence that the self-efficacy beliefs of English as a foreign language (EFL) teachers in East Asian contexts and their second language (L2) proficiency intersect to shape teaching behaviour. However, due to sometimes uncritical use of research instruments developed in the West, imported without sufficient adaptation into Confucian-heritage cultures, the strength of the relationship between EFL teachers' self-efficacy beliefs and their L2 proficiency may be less clear, for example with pre-service teachers (PSTs). As this group is under-researched, it is also less clear how PSTs' self-efficacy beliefs develop during the practicum, shaped by which influences. Set in a Vietnamese context with PSTs drawn from two major universities, our longitudinal mixed methods study addresses these issues. Employing exploratory factor analysis, we reveal dimensions of the PSTs' self-efficacy beliefs. Our correlation and regression analyses then indicate consistent and strong relationships between these beliefs and L2 proficiency, apparently impacted by Vietnamese cultural and contextual factors. Our paired samples t -tests highlight self-efficacy beliefs growth in general pedagogical skills during the practicum, while content analysis of qualitative data reveals the kinds of experiences that impacted change, including those experiences provided by school mentors. Implications for L2 teacher education and research are discussed. Highlights: Dimensions of Vietnamese EFL PST self-efficacy beliefs reflect culture and context. Consistent L2 proficiency and self-efficacy beliefs relationships were identified. The practicum boosted PST self-efficacy beliefs in general pedagogical skills. PST self-efficacy beliefs in language-teaching dimensions were impacted less. Enactive mastery experience over the practicum was reported as the most influential.